Producing long-lived 23S positronium via 33P laser excitation in magnetic and electric fields - Aghion, Stefano; Müller, Simon R.; Oberthaler, Markus K.; Zimmer, Christian (Physical review, 2018)
Producing positronium (Ps) in the metastable 23S state is of interest for various applications in fundamental physics. We report here on an experiment in which Ps atoms are produced in this long-lived state by spontaneous radiative decay of Ps excited to the 33P level manifold. The Ps cloud excitation is obtained with a UV laser pulse in an experimental vacuum chamber in presence of guiding magnetic field of 25mT and an average electric field of 300Vcm−1. The evidence of the 23S state production is obtained to the 3.6σ level of statistical significance using a novel analysis technique of the single-shot positronium annihilation lifetime spectra. The dynamic of the Ps population on the involved levels has been studied with a rate equation model.
Im Titel ist die Zahl "3" hochgestellt
Gesehen am 02.05.2019